The development of a design tool for personal software process (PSP) - Yanawut Chaiyo (2018)
Personal software process (PSP) aims to improve overall process quality for software engineers in an individual level. Designing is an important process in this framework. Yet, evidence reported that PSP design framework can occasionally be repetitive and confusing. This paper describes development of an emerging tool which simplifies and minimizes PSP's design. © 2013 IEEE.